2002
DOI: 10.1210/jc.2002-020687
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 11β-Hydroxysteroid Dehydrogenase Type 1 in Adipose Tissue Is Not Increased in Human Obesity

Abstract: Central obesity is associated with increased morbidity and mortality. Preadipocyte proliferation and differentiation contribute to increases in adipose tissue mass, yet the mechanisms that underlie these processes remain unclear. Patients with glucocorticoid excess develop a reversible form of central obesity, but circulating cortisol levels in idiopathic obesity are invariably normal. We have hypothesized that the enzyme 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1), by converting inactive cortison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
145
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(165 citation statements)
references
References 31 publications
17
145
2
1
Order By: Relevance
“…This suggested that an as yet unidentified post-transcriptional level effect might exaggerate the cortisol reactivation potential of 11 -HSD1 in visceral fat preadipocytes, potentially augmenting the accumulation of visceral adiposity in obesity. This may also occur in human adipose stromal cells which express H6PDH uniformly highly throughout differentiation whilst 11 -HSD1 expression increases (Senesi et al, 2008), although previous studies suggested increasing H6PDH expression may control a switch in enzyme directionality throughout differentiation (Bujalska et al, 2002). Further clarification of this will be needed in human cells.…”
Section: -Hydroxysteroid Dehydrogenase Type 1 In Adipocytesmentioning
confidence: 97%
See 2 more Smart Citations
“…This suggested that an as yet unidentified post-transcriptional level effect might exaggerate the cortisol reactivation potential of 11 -HSD1 in visceral fat preadipocytes, potentially augmenting the accumulation of visceral adiposity in obesity. This may also occur in human adipose stromal cells which express H6PDH uniformly highly throughout differentiation whilst 11 -HSD1 expression increases (Senesi et al, 2008), although previous studies suggested increasing H6PDH expression may control a switch in enzyme directionality throughout differentiation (Bujalska et al, 2002). Further clarification of this will be needed in human cells.…”
Section: -Hydroxysteroid Dehydrogenase Type 1 In Adipocytesmentioning
confidence: 97%
“…In humans, 11 -HSD1 mRNA and activity is increased in subcutaneous abdominal adipose tissue of obese subjects both in vivo and in vitro (Rask et al, 2001, Lindsay et al, 2003, Kannisto et al, 2004, Goedecke et al, 2006, Michailidou et al, 2007, Paulsen et al, 2007 -not a comprehensive list) with few exceptions (Tomlinson et al, 2002).…”
Section: Adipose 11β-hsd1 In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…In men and women with idiopathic obesity it has emerged that there are tissue-specific alterations in 11β HSD-1 activity. Thus, regeneration of cortisol in the liver was decreased [16,17,18], while 11β HSD-1 activity and mRNA were increased in subcutaneous adipose tissue in most [17,18,19,20,21,22], but not all [23], studies. It would be gratifying to extrapolate that 11β HSD-1 is also increased in omental adipose tissue in obesity, and many authors have written as though this had already been documented.…”
mentioning
confidence: 92%
“…Most groups have not attempted to biopsy omental adipose and have restricted their observations to subcutaneous fat. Stewart's group studied omental adipose tissue obtained during surgery and reported that 11β HSD-1 mRNA in freshly isolated tissue did not predict obesity, while enzyme activity and mRNA in cells cultured from omental fat are inversely associated with indices of central obesity [23]. However, in the same subjects, 11β HSD-1 mRNA in subcutaneous abdominal fat was not correlated with obesity either, suggesting that the removal of biopsies during major surgery obscures the relationships that several other groups have found in biopsies obtained electively with local anaesthesia.…”
mentioning
confidence: 99%